(untitled) (Research, Society and Development, 2020)
Objective: to analyze collaborative team work in actions directed to the population in psychosocial care under the focus of integrality. Method: exploratory, descriptive study with a qualitative approach, carried out with nine professionals from a Psychosocial Care Center. The empirical material was produced through reflection workshops and analyzed using the discourse analysis technique. Results: professionals recognize the power of teamwork as a result of interaction, resulting from the sharing of different knowledge and the collaborative team, from the doorman to the coordination. This interaction is reflected in successful experiences, which carry the marks of interprofessionality and integrality. Final considerations: Teamwork is achieved through know-how-to-deal under common objectives centered on attention to the needs of users. The practice is supported by dialogue, collaboration and respect for singularities, with responsibility in shared care. The team’s interaction mobilizes care that transforms people and refreshes practices, which promotes quality psychosocial care.